A Monte Carlo study of the three-dimensional XY universality class: universal amplitude ratios - Hasenbusch, Martin (Journal of statistical mechanics: theory and experiment, 2008)
We simulate lattice models in the three-dimensional XY universality class in the low and the high temperature phase. In addition to the XY model, we study the three-dimensional two-component ϕ4 model on the simple cubic lattice. The parameter of the ϕ4 model is chosen such that leading corrections to scaling are small. This allows us to compute a number of universal amplitude ratios with unprecedented precision: Rϒ = 0.411(2), RB = 2.83(1), Rξ+ = 0.3562(10) and Rξ− = 0.850(5). These results can be compared with those obtained from other theoretical methods, such as field theoretic methods or the high temperature series expansion and also with experimental results for the λ-transition of 4He.
Gesehen am 09.09.2022